Sex steroid hormones in depressive disorders as a basis for new potential treatment strategies - Pillerová, M; Pastorek, M; Borbélyová, V; Riljak, V; Frick, K M; Hodosy, J; Tóthová, L (Physiological research, 2022)
The sex steroid hormones (SSHs) such as testosterone, estradiol, progesterone, and their metabolites have important organizational and activational impacts on the brain during critical periods of brain development and in adulthood. A variety of slow and rapid mechanisms mediate both organizational and activational processes via intracellular or membrane receptors for SSHs. Physiological concentrations and distribution of SSHs in the brain result in normal brain development. Nevertheless, dysregulation of hormonal equilibrium may result in several mood disorders, including depressive disorders, later in adolescence or adulthood. Gender differences in cognitive abilities, emotions as well as the 2-3 times higher prevalence of depressive disorders in females, were already described. This implies that SSHs may play a role in the development of depressive disorders. In this review, we discuss preclinical and clinical studies linked to SSHs and development of depressive disorders. Our secondary aim includes a review of up-to-date knowledge about molecular mechanisms in the pathogenesis of depressive disorders. Understanding these molecular mechanisms might lead to significant treatment adjustments for patients with depressive disorders and to an amelioration of clinical outcomes for these patients. Nevertheless, the impact of SSHs on the brain in the context of the development of depressive disorders, progression, and treatment responsiveness is complex in nature, and depends upon several factors in concert such as gender, age, comorbidities, and general health conditions.
Keywords: emoce; Brain; Gonadal Steroid Hormones; ženské pohlaví; Testosterone; Emotions; pohlavní steroidní hormony; mozek; Humans; pohlavní dimorfismus; depresivní poruchy; Female; Sex Characteristics; Adolescent; Depressive Disorder; lidé; testosteron; mladiství